Primary care physicians' willingness to disclose oncology errors involving multiple providers to patients. Issue 10 (3rd November 2015) - Mazor, Kathleen; Roblin, Douglas W; Greene, Sarah M; Fouayzi, Hassan; Gallagher, Thomas H
Abstract : Background: Full disclosure of harmful errors to patients, including a statement of regret, an explanation, acceptance of responsibility and commitment to prevent recurrences is the current standard for physicians in the USA. Objective: To examine the extent to which primary care physicians' perceptions of event-level, physician-level and organisation-level factors influence intent to disclose a medical error in challenging situations. Design: Cross-sectional survey containing two hypothetical vignettes: (1) delayed diagnosis of breast cancer, and (2) care coordination breakdown causing a delayed response to patient symptoms. In both cases, multiple physicians shared responsibility for the error, and both involved oncology diagnoses. Setting: The study was conducted in the context of the HMO Cancer Research Network Cancer Communication Research Center. Participants: Primary care physicians from three integrated healthcare delivery systems located in Washington, Massachusetts and Georgia; responses from 297 participants were included in these analyses. Main measures: The dependent variable intent to disclose included intent to provide an apology, an explanation, information about the cause and plans for preventing recurrences. Independent variables included event-level factors (responsibility for the event, perceived seriousness of the event, predictions about a lawsuit); physician-level factors (value of patient-centred communication, communication self-efficacy and feelings about practice); organisation-level factors included perceived support for communication and time constraints. Key results: A majority of respondents would not fully disclose in either situation. The strongest predictors of disclosure were perceived personal responsibility, perceived seriousness of the event and perceived value of patient-centred communication. These variables were consistently associated with intent to disclose. Conclusion: To make meaningful progress towards improving disclosure; physicians, risk managers, organisational leaders, professional organisations and accreditation bodies need to understand the factors which influence disclosure. Such an understanding is required to inform institutional policies and provider training.